Surgical Atlas of Sports Orthopaedics and Sports Traumatology - Imhoff, Andreas B.; Feucht, Matthias J. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This atlas depicts and describes the newest arthroscopic and open techniques for dealing with sports orthopaedic injuries and problems. More than 75 surgical procedures are presented step by step with the aid of superb illustrations. Arthroscopic views, artist drawings, X-rays, and clinical and operative photographs are all included to demonstrate exactly how each procedure should be performed. Individual sections are devoted to the shoulder, elbow, pelvis/hip, knee, and ankle/foot. By offering complete illustrated guidance on the surgical management of sports-related injuries, the Surgical Atlas of Sports Orthopaedics and Sports Traumatology will prove invaluable to both novice and experienced surgeons.